Plant regeneration through somatic embryogenesis in Quercus suber - Bueno, M. A.; Astorga, R.; Manzanera, J. A. (Physiologia Plantarum, 1992)
Cork oak (Quercus suber L.) zygotic embryos, endosperm and ovules were treated with different concentrations of 2,4-D for induction of somatic embryos. Plant material was collected during the embryo development season, from June to September. Immature embryos proved to be the most reactive initial explant. Callus and somatic embryos developed a few weeks after the beginning of the 2,4-D treatment. For embryo development experiments, different growth regulators and cold and desiccation treatments were tested. Cold storage of somatic embryos matured in vitro at 5°C was the best treatment for breaking dormancy.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Cork oak; plant regeneration; Quercus suber; Somatic embryogenesis; tissue culture